Characteristics Analysis of Modification Asbuton Granular B 50/30 With Asphalt Pen 60/70 - Ari Sujiartono; Sri Wiwoho Mudjanarko (LPPM of NAROTAMA UNIVERSITY, 2022)
In the framework of handling the bending pavement road, natural materials in the form of asphalt as a binding material in a hot paved blend are needed. One of the abundant natural asphaltic that has not been used to its fullest is Asbuton. The government through the Ministry of Public Works which is currently transformed into the Ministry of Public Works and Public Housing has issued Public Works Regulation No. 35 of 2006 on Increasing the Utilization of Buton Asphalt for Road Maintenance and Development. Because various things that cause permission to use 100% Asbuton in hot paved blends can not be issued, the use of Asbuton is still limited to improving the quality of asphalt Pen 60/70. This research aims to obtain an optimal composition in the use of Asbuton using the type of Asbuton Grain B 50/30. It is hoped that the results of the research can be an additional reference for Asbuton producers as well as a new insight for civil engineering students who explore the path of bending pavement. The results showed that Asbuton Granular B 50/30 can be used in improving the quality of Asphalt Pen 60/70 with an optimal composition of 25% Asbuton Granular B 50/30 and 75% Asphalt Pen 60/70.